On the Security of NOEKEON against Side Channel Cube Attacks - Abdul-Latip, S. F.; Reyhanitabar, M. R.; Susilo, W.; Seberry, J. (Springer Berlin / Heidelberg, 2010)
In this paper, we investigate the security of the NOEKEON block cipher against side channel cube attacks. NOEKEON was proposed by Daemen et al. for the NESSIE project. The block size and the key size are both 128 bits. The cube attack, introduced by Dinur and Shamir at EUROCRYPT 2009, is a new type of algebraic cryptanalysis. The attack may be applied if the adversary has access to a single bit of information that can be represented by a low degree multivariate polynomial over GF(2) of secret and public variables. In the side channel attack model, the attacker is assumed to have access to some leaked information about the internal state of the cipher as well as the plaintext and ciphertext. Adopting the notion of a single bit leakage as formalized by Dinur and Shamir, we assume that the attacker has only one bit of information about the intermediate state after each round. Using this side channel attack model, we show that it is possible to extract 60 independent linear equations over 99 (out of 128) key variables. To recover the whole 128-bit key, the attack requires only about 210 chosen plaintext and O(268) time complexity.